Improving warehouse layout design of a chicken slaughterhouse using combined ABC class based and optimized allocation techniques - Tippayawong K.Y. (2014)
This paper was about analyzing and designing appropriate warehouse operation of a representative meat product factory. A chicken slaughterhouse was chosen as a case study. ABC class-based storage policy and optimized product allocation using linear programming were combined and used to design an improved warehouse layout. The product circulation ratio was considered. Results indicated that the combined technique offers significant improvement to the existing layout. Reductions of the overall travel distance during operation by almost 45% or over 6,000 m a day and the picking time by 42% can be achieved. Projected increases in the space utilization performance and the inventory service level are 45 and 28%, respectively. When proposed layout and picking system are implemented, attractive return on investment can be realized with discounted payback period of less than one and half year.